Retrial According to Provisions of Code of Civil Procedure from 1865 - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
The article sheds light on provisions of legislation from 1865 concerning retrial as sole extraordinary legal remedy, its amendments and supplements, as well as judicial practice regarding repetition of judicial proceedings. Party in a civil lawsuit entitled to remedy was the plaintiff who had been considering himself aggrieved by a court decision from which no appeal was longer allowed, and who came into possession of new and important matter of evidence. It is necessary that, at the time when a decision was passed, that evidence, after the excercise of due dilligence, was not within his knowledge or could not be produced by him. Party might apply for a retrial only if there is strict proof for such allegation. Otherwise, when it appears to the court that there was not sufficient ground for a retrial, application would be rejected. Besides additional evidence, the paper also deals with other reasons to apply for a retrial, such as errors in judicial procedure and unlawfulnesses in court decisions. The author emphasizes that, according to provisions of Code from 1865, retrial could not had been granted without previous notice to the opposite party; nor could be retried lawsuit that had been adjusted by lawful agreement or compromise, with notably rare exceptions. This aforementioned restrictions in application of legal remedy were vitally important for preserving judicial authority, court efficiency and principle of legal certainty.